Assessing cationic dye adsorption mechanisms on MIL-53 (Al) nanostructured MOF materials using quantum chemical and molecular simulations: Toward environmentally sustainable wastewater treatment - Salahshoori, Iman; Namayandeh Jorabchi, Majid; Ghasemi, Somayeh; Mirnezami, Seyedeh Masoomeh Sadat; Nobre, Marcos A.L. [UNESP]; Khonakdar, Hossein Ali (Elsevier, 2023)
The escalating levels of environmental pollutants, particularly cationic dyes, present a significant ecological threat. Cationic dyes such as rhodamine B (RB) and methylene blue (MB) are extensively used in diverse industrial applications and are known to exert detrimental effects on the environment. The focus of this study revolves around comprehensively examining the adsorption mechanisms associated with the binding of cationic dyes, namely, RB and MB, onto pristine and carboxylic acid (CXA)-modified MIL-53 (Al) nanostructures. By employing quantum mechanics and molecular simulations, this research elucidates the molecular-level behavior of materials and dyes during the adsorption process. The findings demonstrate that incorporating CXA groups enhances MIL-53 (Al)'s adsorption capacity for both RB and MB dyes. Furthermore, the simulations unveil that RB and MB dye adsorption onto the unmodified and modified MIL-53 (Al) materials occurs primarily through electrostatic, van der waals interactions, π-π stacking, and hydrogen bonding. Notably, RB dye exhibits superior reactivity and stability compared to MB dye, owing to its higher adsorption energy. This study provides valuable insights into cationic dye adsorption on nanostructured MIL-53 (Al), emphasizing the suitability of CXA-modified MIL-53 (Al) nanostructures for cationic dye removal from contaminated wastewater. The outcomes of this investigation hold the potential for developing cutting-edge technologies exhibiting superior efficiency and effectiveness for removing cationic dyes, thereby contributing to environmental preservation and public health. Ultimately, this study highlights the prospects of leveraging quantum mechanics and molecular simulations to anticipate the behavior of nanostructured materials and optimize their properties for wastewater treatment.
Keywords: Cationic dye adsorption; Environmental pollutants; Metal-organic frameworks; Molecular simulation; Quantum chemical calculations; Wastewater treatment